Eating behavior in rhythmic gymnastics athletes - Francisco, Beatriz Pomini; Souza, Edirley Guimarães de; Santos, Fernando Pereira dos (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 39 No 76 (2023): Publicação Contínua, 2023)
The objective of this work is to identify Gymnasts who suffer from eating disorders and have a distorted view of their bodies. Articles were analyzed with the subject on the food issue in Rhythmic Gymnastics athletes and non-athletes where we were able to conclude that in older athletes and non-athletes the distorted body view ends up being greater. We know that for athletes where their bodies are a showcase, food responsibility and discipline also increase.